Research on optimisation of energy efficient routing protocol based on LEACH. (21st July 2022) - Sun, Haibin; Pan, Dijing
Although the low energy adaptive clustering hierarchy (LEACH) protocol can extend network lifetime, it still has some deficiencies. To further improve the energy efficiency of the network, a new low-power efficient routing protocol based on LEACH (LPE-LEACH) is proposed. Firstly, the optimal number of CHs is analysed by abstracting the network into a mathematical model. Secondly, the threshold for the election of CHs is redefined to guarantee that better nodes can be elected. Besides, spare CHs are introduced to decrease the probability of premature death of CHs. Next, the way ordinary nodes choose their CH is also improved. Last but not least, the method of data transmission is further enhanced. MATLAB simulation experiments show that the protocol extends network lifetime by 85%, 117.6%, 42.3% and 32.1% over LEACH, LEACH-C, LEACH-VA and IEE-LEACH, respectively.